A study of top-down cracking in the state of Oregon. Issue 8 (17th November 2018) - Rahman, Md S.; Podolsky, Joseph H.; Williams, R. Christopher; Scholz, Todd
Abstract : A major concern from the Oregon Department of Transportation (ODOT) in recent years has been the prevention of top-down cracking in HMA pavements shortly into their design lives. To this end, the ODOT has identified hot mix asphalt (HMA) pavements that have displayed top-down cracking within three years of construction for evaluation. This study's main objective is the evaluation of top-down cracked pavement sections against results collected from non-cracked pavement sections, and the identification of practices that will prevent top-down cracking from occurring. Six surface cracked pavements and four non-cracked pavement sections were used for conducting this research. Extensive field and laboratory investigations were done through distress surveys, falling weight deflectometer testing, dynamic cone penetrometer (DCP) testing, coring from cracked and non-cracked pavement sections, and testing of cores for HMA mixture rheology and asphalt binder rheology. The laboratory investigation included dynamic modulus, indirect tensile strength, and specific gravity testing on the HMA cores, rheological tests on asphalt binder and aggregate gradation analysis. Results suggest that prevention of top-down cracking can be improved through tighter control on density (air void requirements) and asphalt binder selection during material selection and initial construction.